2020
DOI: 10.4269/ajtmh.19-0717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Frijoles and Chilibre Species Complex Viruses (Genus Phlebovirus; Family Phenuiviridae) and Three Unclassified New World Phleboviruses

Abstract: The genus Phlebovirus is a diverse group of globally occurring viruses, including tick-, mosquito-, and sand fly-borne pathogens. Phleboviruses have historically been classified by serological methods. However, molecular methods alone have been used to identify emergent novel and related strains in recent years. This makes reconciling the classification of historically and newly characterized viruses challenging. To address this in part, we describe the characterization of the genomes of the Frijoles and Chili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The preGP also shows a strong phylogenetic relationship with Pacuvirus and Orthobunyavirus in group VI. This ML analysis supports the suggestion that the taxonomic identity for CHIV should be moved from the Phlebovirus to the Pacuvirus genus within Peribunyaviridae [ 54 ]. Inter-lineage reassortment, although unlikely, may only be considered for the assignment of Chilibre virus because these viruses share common reservoirs [ 55 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The preGP also shows a strong phylogenetic relationship with Pacuvirus and Orthobunyavirus in group VI. This ML analysis supports the suggestion that the taxonomic identity for CHIV should be moved from the Phlebovirus to the Pacuvirus genus within Peribunyaviridae [ 54 ]. Inter-lineage reassortment, although unlikely, may only be considered for the assignment of Chilibre virus because these viruses share common reservoirs [ 55 ].…”
Section: Discussionsupporting
confidence: 82%
“…Members of the genus Phlebovirus are viruses that are borne by ticks, mosquitoes, and sandflies. Prior molecular characterization suggested that CHIV may be more related to the genus Pacuvirus within Peribunyaviridae [ 54 ]. Our ML analysis using a much larger dataset indicates that CHIV RdRp and N proteins share a specific relationship with the Pacuvirus within the Group I Peribunyaviridae.…”
Section: Discussionmentioning
confidence: 99%
“…Following isolation, identification and characterization of newly derived isolates were formerly provided by predominantly antibody-based methods, including complement fixation (CF), hemagglutination inhibition (HI), immunofluorescence assays (IFAs), and plaque reduction neutralization tests (PRNTs) [ 7 , 17 ]. In recent years, isolates have become increasingly characterized by nucleic-acid-based methods [ 18 , 19 , 20 ], including whole-genome sequencing, rather than serology. This transition has facilitated the more rapid identification of reassortant viruses [ 4 , 21 ] and allows for taxonomic classification based upon nucleic-acid-based criteria for demarcation [ 1 ].…”
Section: Methods For the Detection Of Phleboviruses And Their Infectionsmentioning
confidence: 99%
“…Viruses within the genus Phlebovirus, family Phenuiviridae, include mosquito-, sand fly-, and tick-borne pathogens, and these viruses have three negative sense RNA segments (4). The first phlebovirus identified in the United States, Rio Grande virus (RGV), was isolated from southern plains woodrats (Neotoma micropus) in Texas [1,2], and was shown to be transmitted by a sand fly, Lutzomyia anthophora, in the laboratory [3].…”
Section: Introductionmentioning
confidence: 99%
“…No antibodies were found in 278 human serum samples tested, and sera from native wild ruminants were not tested [ 1 ]. Rio Grande virus is phylogenetically related to Anhanga virus, and is also grouped with Tapara virus in analyses based on the nucleocapsid protein (NP) [ 4 ]. Neotoma micropus , thought to be the natural host, ranges across North America from southeastern Colorado, east to central Kansas, west to the Arizona border, and south to the eastern coast of Mexico in northern Veracruz [ 5 ].…”
Section: Introductionmentioning
confidence: 99%